International Agreements Regulated by European Directives (Private International Law) - Aguilar Grieder, Hilda (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This study analyses the law applicable treatment to the international agreements regulated by European Directives. It is necessary to find a solution to that problem in the frame of the European Private International Law.
Keywords: European Private International Law; international agreements; European Directives; conflict of law solutions; “Rome I” Regulation on the law applicable to contractual obligations